2001
DOI: 10.1097/00005537-200112000-00025
|View full text |Cite
|
Sign up to set email alerts
|

The Sternocleidomastoid Flap—Its Indications and Limitations

Abstract: The data presented in previous literature is well correlated with our own morphologic findings. In comparison of the different techniques applied with the assumptions drawn on the basis of our own anatomic findings, it becomes evident that the SCM flap is only a useful tool in limited indications and under certain precautions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 26 publications
3
51
1
2
Order By: Relevance
“…The SCM flap may be used as a composite or muscle flap in some defects. High levels of blood supply to the SCM muscle facilitate the preparation of the SCM muscle flap with both superior and inferior pedicles (32). In parotidectomy, SCM muscle flap was first used by Kornblut et al (31).…”
Section: Discussionmentioning
confidence: 99%
“…The SCM flap may be used as a composite or muscle flap in some defects. High levels of blood supply to the SCM muscle facilitate the preparation of the SCM muscle flap with both superior and inferior pedicles (32). In parotidectomy, SCM muscle flap was first used by Kornblut et al (31).…”
Section: Discussionmentioning
confidence: 99%
“…While many authors address the multilayered structure of the defect [13], only one report on free vascularized bone transfer was found [8]. The concept of a regional myo-osteous flap of the neck was described by the myo-osteous sternocleidohyoideous flap for mandibular reconstruction in a review article by Kierner et al [9]. In partial closure of a tracheostoma (type IV), a bone chip allows reliable intraoperative determination of the resulting stoma size; the concomitant adipocutaneous part of the flap allows reconstruction of the surrounding tissue by providing soft tissue padding and improved appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the final aesthetic result is of great importance because of the visibility of the suprasternal notch. Several procedures have been advocated for closure, including multilayered advancement flaps [7,13], sternocleidomastoid muscle flaps [9], free cartilage transfer [17,2], and free flap surgery [8,3].…”
Section: Introductionmentioning
confidence: 99%
“…They also reported in their literature review a 21% (29 out of 138 patients) failure rate if the fl ap was taken as myocutaneous version with partial skin necrosis was the most frequent, seven fl aps showed total failure, fl ap necrosis was reported in one patient (4%) out of 23 osteomuscular SCM fl ap. 18 Siemsson et al reported one failure out of 18 splitted clavicular head of SCM used to repair laryngeal and tracheal defects leaving the sternal head 19 and, according to Watkinson JC et al, the fl ap is rarely used now, but it may still have a role to play fi lling small defects in pharynx and oral cavity, and to cover vessels in the compromised neck. 4 According to a blood supply cadaveric study done by Kierner et al, 20 he had a general agreement that the blood supply of the SCM comes from 3 main arteries described in other main studies, 16,21 for the upper third it is supplied mainly by occipital artery which is further divided into 3 categories smaller upper branches representing 87%, and a single well-developed branch on 33 to 39%, this branch goes with the accessory nerve in 19 to 27%, for the middle third blood supply, the study shows some variability, it concluded that about 50% of cases are supplied directly by the external carotid artery, and in 67 to 71% have branches from superior thyroid artery, and in more than 80% of cases, the lower third of the muscle is supplied by suprascapular artery.…”
Section: Sternocleidomastoid Flapmentioning
confidence: 99%